Firm-level technology adoption in times of crisis - Melanie Arntz; Michael Böhm; Georg Graetz; Terry Gregory; Florian Lehmer; Cäcilia Lipowski (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This study investigates how crises affect firms' adoption of frontier technologies using the Covid-19 pandemic as a case study. The analysis tracks the nature, timing, and pandemic-related motivations of investments among German firms, using longitudinal survey data linked with administrative worker-firm records. We find clear evidence for a shift toward remote work technologies that helped firms mitigate negative employment effects. Overall, however, the pandemic slowed down the diffusion of new technologies. This procyclical pattern of technology adoption is particularly striking since the pandemic created strong incentives to experiment with new technologies.
Keywords: O33; E22; E32; J23; 330; Firm-level technology investments; cyclicality of technology adoption; Covid-19 crisis